Channel optimization of high-intensity laser beams in millimeter-scale plasmas - Ceurvorst, L; Savin, A; Ratan, N; Sadler, James; Norreys, PA; Habara, H; Tanaka, KA; Zhang, S; Wei, MS; Ivancic, S; Froula, D; Theobald, W (American Physical Society, 2018)
Channeling experiments were performed at the OMEGA EP facility using relativistic intensity ( > 10 18 W / cm 2 ) kilojoule laser pulses through large density scale length ( ∼ 390 – 570 μ m ) laser-produced plasmas, demonstrating the effects of the pulse's focal location and intensity as well as the plasma's temperature on the resulting channel formation. The results show deeper channeling when focused into hot plasmas and at lower densities, as expected. However, contrary to previous large-scale particle-in-cell studies, the results also indicate deeper penetration by short (10 ps), intense pulses compared to their longer-duration equivalents. This new observation has many implications for future laser-plasma research in the relativistic regime.